META-ANALISIS EFEKTIVITAS PEMBELAJARAN MATEMATIKA BERBASIS STEAM TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI INDONESIA - Naila Nabila Fauziyah; Bambang Sri Anggoro; Dona Dinda Pratiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of STEAM-based mathematics learning on students' mathematical problem-solving abilities in Indonesia. The method used was a meta-analysis of research results published nationally in 2021–2025. Data were collected through a literature review using Google Scholar with the help of the Publish or Perish application. Of the 997 scientific papers found, 6 scientific papers met the criteria and were further analyzed. Quantitative descriptive statistical analysis was used to obtain the effect size value. The results showed that STEAM-based mathematics learning had a very high influence on students' mathematical problem-solving abilities, with an effect size value of 1.480. The effectiveness of this learning varied by educational level, which was influenced by student characteristics, implementation readiness, learning models and media, and the approach to teaching material development. The highest effectiveness was found at the elementary school level.